Copper-containing oriented silicon steel and preparation method thereof

By controlling the composition and process steps of the slab, a suitable oxide layer and a magnesium silicate bottom layer are formed, which solves the problem of difficult control of the surface quality of copper-containing oriented silicon steel, and improves magnetic properties and insulation.

CN119287125APending Publication Date: 2025-01-10HUNAN VALIN LIANYUAN IRON & STEEL CO LTD +1
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
CN202411353982.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-26
Publication Date
2025-01-10

AI Technical Summary

Technical Problem

In the existing secondary cold rolling process of copper-oriented silicon steel, the oxide layer is destroyed after the first cold rolling, resulting in difficult control of the surface quality and difficult to improve the bottom layer quality, which affects the insulation and magnetic properties of the transformer core. .

Method used

By controlling the Al, N, Cu and Cr content in the slab, hot rolling, first cold rolling, decarbonization annealing and second cold rolling treatments are performed to form a suitable oxide layer, followed by magnesium oxide layer and high temperature annealing. , coating the insulating layer and stretching and flat annealing to optimize the formation of the magnesium silicate bottom layer.

Benefits of technology

The bottom layer and surface quality of copper-containing oriented silicon steel is improved, magnetic induction strength and insulation are improved, iron loss is reduced, and surface gloss and adhesion is improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119287125A_ABST
    Figure CN119287125A_ABST
Patent Text Reader

Abstract

The invention discloses copper-containing oriented silicon steel and a preparation method thereof. The preparation method comprises the steps that a plate blank of the copper-containing oriented silicon steel is provided, and the plate blank comprises the following components by taking the total mass of the plate blank as 100%: 0.03%-0.06% of C, 2.85%-3.45% of Si, 0.03%-0.06% of Si, 0.03%-0.06% of Cr, 0.03%-0.06% The steel comprises the following components in percentage by weight: 0.015%-0.025% of Als, 0.0075%-0.0115% of N, 0.1%-0.3% of Mn, 0.4%-0.6% of Cu, 0.003%-0.010% of S, 0.05%-0.20% of Cr and the balance of Fe and inevitable impurities. The plate blank is subjected to hot rolling treatment, hot-rolled strip steel is obtained, and the heating temperature of hot rolling treatment ranges from 1250 DEG C to 1320 DEG C; carrying out primary cold rolling treatment on the hot-rolled strip steel to obtain the strip steel subjected to primary cold rolling; and the strip steel subjected to primary cold rolling is subjected to decarburization annealing treatment, the strip steel subjected to decarburization annealing is obtained, the oxygen content of the strip steel subjected to decarburization annealing is 550-750 ppm, and the thickness of an oxide layer of the strip steel subjected to decarburization annealing is 7-9 microns. According to the copper-containing oriented silicon steel and the preparation method thereof, the bottom layer quality of the copper-containing oriented silicon steel can be improved, and therefore the surface quality of the copper-containing oriented silicon steel is improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the technical field of oriented silicon steel preparation, and in particular to a copper-containing oriented silicon steel and a preparation method thereof. Background Art

[0002] Oriented silicon steel is an important soft magnetic functional material, mainly used as various transformer cores. In addition to having good magnetic properties, oriented silicon steel must also have excellent surface quality so that the transformer core made of it has interlayer insulation. However, the premise of obtaining good surface quality is to obtain excellent bottom layer quality. The bottom layer formation process of oriented silicon steel is very complicated. First, an oxide layer is formed by decarburization annealing, and then a magnesium oxide coating is applied. The type, quality, coating process and drying process of the coating will affect the bottom layer quality. Finally, high-temperature annealing is performed to react magnesium oxide with silicon dioxide to form a magnesium silicate bottom layer.

[0003] Oriented silicon steel is divided into high magnetic induction oriented silicon steel and ordinary oriented silicon steel. Ordinary copper-containing oriented silicon steel adopts the production process of double cold rolling. Compared with the production process of single cold rolling, the oxide layer is formed in the decarburization annealing stage after the first cold rolling. The second cold rolling will destroy the oxide layer, which will eventually affect the surface quality of copper-containing oriented silicon steel. Therefore, the bottom layer quality of the double cold rolling production process is more difficult to control, and it is urgent to improve the surface quality of the oxide layer of copper-containing oriented silicon steel. Summary of the invention

[0004] The embodiments of the present application provide a copper-containing oriented silicon steel and a preparation method thereof, which can improve the bottom layer quality of the copper-containing oriented silicon steel, thereby improving the surface quality of the copper-containing oriented silicon steel.

[0005] In a first aspect, an embodiment of the present application proposes a method for preparing copper-containing oriented silicon steel, comprising: providing a slab of copper-containing oriented silicon steel, wherein the slab comprises the following components, based on the total mass of the slab as 100%, C: 0.03%-0.06%, Si: 2.85%-3.45%; Als: 0.015%-0.025%, N: 0.0075%-0.0115%, Mn: 0.1%-0.3%, Cu: 0.4%-0.6%, S: 0.003%-0.010%, Cr: 0.05%-0.20%, and the rest is Fe and inevitable impurities; the slab is hot rolled to obtain hot rolled strip steel, and the heating temperature of the hot rolling treatment is 1250-1320℃; the hot rolled strip steel is cold rolled for the first time to obtain the first cold rolled strip steel; the first cold rolled strip steel is decarburized annealed to obtain the decarburized annealed strip steel, the oxygen content in the decarburized annealed strip steel is 550-750ppm, and the oxide layer thickness of the decarburized annealed strip steel is 7-9μm.

[0006] According to one aspect of the embodiment of the present application, the step of hot rolling the slab to obtain the hot rolled strip also includes: the final rolling temperature of the hot rolling treatment is 890-990°C.

[0007] According to one aspect of an embodiment of the present application, the step of performing a first cold rolling treatment on the hot-rolled strip to obtain the first cold-rolled strip includes: the thickness of the first cold-rolled strip is 0.5-0.8 mm.

[0008] According to one aspect of an embodiment of the present application, the step of performing decarburization annealing on the steel strip after the first cold rolling to obtain the decarburization annealed steel strip includes: the temperature of the decarburization annealing is 790-890°C.

[0009] According to one aspect of an embodiment of the present application, in the step of performing decarburization annealing on the steel strip after the first cold rolling to obtain the steel strip after decarburization annealing, the carbon content in the steel strip after decarburization annealing is less than 30 ppm.

[0010] According to one aspect of an embodiment of the present application, the preparation method further includes performing a second cold rolling treatment on the steel strip after decarburization annealing to obtain the steel strip after the second cold rolling.

[0011] According to one aspect of an embodiment of the present application, in the step of performing a second cold rolling treatment on the strip steel after decarburization annealing to obtain the strip steel after the second cold rolling, the thickness of the strip steel after the second cold rolling is 0.18-0.30 mm.

[0012] According to one aspect of an embodiment of the present application, the preparation method further includes: coating the steel strip after the second cold rolling with a magnesium oxide layer, high temperature annealing, coating with an insulating layer, stretching and flattening annealing, and laser scoring.

[0013] In a second aspect, an embodiment of the present application proposes a copper-containing oriented silicon steel, which is prepared by the preparation method of the first aspect of the present application.

[0014] According to another aspect of the embodiment of the present application, the iron loss of the copper-containing oriented silicon steel is 0.78-1.02 W / kg, and the magnetic induction intensity of the copper-containing oriented silicon steel is greater than 1.89 T.

[0015] In the embodiment of the present application, by controlling the mass content of Als in the copper-containing oriented silicon steel within the range of 0.015%-0.025%, and controlling the mass content of N within the range of 0.0075%-0.0115%, the AlN in the slab can be completely dissolved during the hot rolling treatment, and can also play a role in inhibiting the growth of primary grains before the start of secondary recrystallization. Controlling the mass content of Cu within the range of 0.4%-0.6% can promote the precipitation of AlN after hot rolling treatment and decarburization annealing. Controlling the mass content of Cr within the range of 0.05%-0.20% can increase the thickness of the oxide layer and improve the structure of the oxide layer. By controlling the heating temperature of the hot rolling treatment within the range of 1250-1320°C, the complete solid solution of AlN can be promoted. By controlling the oxygen content in the strip after decarburization annealing within the range of 550-750ppm, a suitable oxide layer thickness can be obtained. Controlling the oxide layer thickness of the strip steel after decarburization annealing within the range of 7-9 μm can improve the bottom layer quality of the copper-containing oriented silicon steel, thereby improving the surface quality of the copper-containing oriented silicon steel. BRIEF DESCRIPTION OF THE DRAWINGS

[0016] The features, advantages and technical effects of exemplary embodiments of the present application will be described below with reference to the accompanying drawings.

[0017] Figure 1 A schematic flow chart of a method for preparing copper-containing oriented silicon steel provided in some embodiments of the present application;

[0018] Figure 2 This is a schematic diagram of the oxide layer structure of the steel strip after decarburization annealing treatment in Example 2 of the present application;

[0019] Figure 3 This is a schematic diagram of the oxide layer structure of the steel strip after decarburization annealing treatment in Comparative Example 1 of the present application. DETAILED DESCRIPTION

[0020] The features and exemplary embodiments of various aspects of the present application will be described in detail below. In order to make the purpose, technical solutions and advantages of the present application clearer, the present application will be further described in detail below in conjunction with the accompanying drawings and specific embodiments. It should be understood that the specific embodiments described herein are only intended to explain the present application, rather than to limit the present application. For those skilled in the art, the present application can be implemented without the need for some of these specific details. The following description of the embodiments is only to provide a better understanding of the present application by illustrating the examples of the present application. In addition, the features, structures or characteristics described hereinafter may be combined in one or more embodiments in any suitable manner.

[0021] It should be noted that, in this application, the term "comprises" or any other variant thereof is intended to cover non-exclusive inclusion, so that a process, method, article or device including a series of elements includes not only those elements, but also includes other elements not explicitly listed, or also includes elements inherent to such process, method, article or device. In the absence of further restrictions, the elements defined by the sentence "comprises..." do not exclude the existence of other identical elements in the process, method, article or device including the elements.

[0022] Unless otherwise specified, the values ​​of the parameters mentioned in this application can be measured by various measurement methods commonly used in the art (for example, they can be tested according to the methods given in the examples of this application). Unless otherwise specified, the test temperature of the parameters mentioned in this application is 25° C. and the test pressure is standard atmospheric pressure.

[0023] As described in the background technology section, ordinary copper-containing oriented silicon steel adopts the secondary cold rolling production process. The oxide layer is formed in the decarburization annealing stage after the first cold rolling. The second cold rolling will destroy the oxide layer. The thickness and structure of the oxide layer have an important influence on the formation of the bottom layer, thereby affecting the surface quality of copper-containing oriented silicon steel. Higher requirements are put forward for the surface quality in the secondary cold rolling preparation process, specifically, the coating has good adhesion to the substrate, the surface gloss is good, and there are no defects such as point-shaped gold exposure and invisible crystal exposure.

[0024] Figure 1 A schematic flow chart of a method for preparing copper-containing oriented silicon steel provided in some embodiments of the present application.

[0025] like Figure 1 As shown, the embodiment of the present application proposes a method for preparing copper-containing oriented silicon steel, comprising the following steps:

[0026] S10: providing a slab of copper-containing oriented silicon steel, wherein the slab comprises the following components based on the total mass of the slab as 100%: C: 0.03%-0.06%, Si: 2.85%-3.45%; Als: 0.015%-0.025%, N: 0.0075%-0.0115%, Mn: 0.1%-0.3%, Cu: 0.4%-0.6%, S: 0.003%-0.010%, Cr: 0.05%-0.20%, and the remainder is Fe and unavoidable impurities;

[0027] S20: hot rolling the slab to obtain hot-rolled strip steel, wherein the heating temperature of the hot rolling treatment is 1250-1320° C.;

[0028] S30: performing a first cold rolling process on the hot-rolled steel strip to obtain a first cold-rolled steel strip;

[0029] S40: performing decarburization annealing treatment on the steel strip after the first cold rolling to obtain a steel strip after decarburization annealing, wherein the oxygen content in the steel strip after decarburization annealing is 550-750 ppm, and the thickness of the oxide layer of the steel strip after decarburization annealing is 7-9 μm.

[0030] In the embodiment of the present application, by controlling the mass content of Als in the copper-containing oriented silicon steel within the range of 0.015%-0.025%, and controlling the mass content of N within the range of 0.0075%-0.0115%, the AlN in the slab can be completely dissolved during the hot rolling treatment, and can also play a role in inhibiting the growth of primary grains before the start of secondary recrystallization. Controlling the mass content of Cu within the range of 0.4%-0.6% can promote the precipitation of AlN after hot rolling treatment and decarburization annealing. Controlling the mass content of Cr within the range of 0.05%-0.20% can increase the thickness of the oxide layer and improve the structure of the oxide layer. By controlling the heating temperature of the hot rolling treatment within the range of 1250-1320°C, the complete solid solution of AlN can be promoted. By controlling the oxygen content in the strip after decarburization annealing within the range of 550-750ppm, a suitable oxide layer thickness can be obtained. Controlling the oxide layer thickness of the strip steel after decarburization annealing within the range of 7-9 μm can improve the bottom layer quality of the copper-containing oriented silicon steel, thereby improving the surface quality of the copper-containing oriented silicon steel.

[0031] It should be noted that the oxygen content in the strip after decarburization annealing is the oxygen content on the surface of the strip, and the oxygen content in the strip after decarburization annealing can further reflect the thickness of the oxide layer of the strip. When the oxygen content is less than 550ppm, the surface gloss of the copper-containing oriented silicon steel will be poor, and when the oxygen content is greater than 750ppm, point-shaped gold leakage defects are prone to occur.

[0032] The main components of the oxide layer include FeO, Fe2SiO4 and SiO2.

[0033] In addition, when the Cr content is greater than 0.2%, the surface of the strip will turn black after pickling, which will deteriorate the surface quality of copper-containing oriented silicon steel. When the oxide layer thickness is less than 7μm, the insulation coating adhesion of copper-containing oriented silicon steel is poor. When the oxide layer thickness is greater than 9μm, the decarburization annealing time needs to be extended, resulting in reduced production efficiency.

[0034] In some optional embodiments, the step of hot rolling the slab to obtain the hot rolled strip further comprises: the final rolling temperature of the hot rolling process can be 890-990°C.

[0035] In some optional embodiments, the thickness of the steel strip after hot rolling may be 2.0-2.5 mm.

[0036] In some optional embodiments, the preparation method further comprises pickling the hot-rolled strip.

[0037] In some optional embodiments, the step of performing a first cold rolling treatment on the hot-rolled steel strip to obtain the first cold-rolled steel strip includes: the thickness of the first cold-rolled steel strip can be 0.5-0.8 mm.

[0038] The thickness of the strip can be reduced by performing the first cold rolling treatment on the hot-rolled strip. By controlling the thickness of the strip after the first cold rolling within the above range, it is beneficial to the subsequent decarburization annealing treatment and improves the magnetic properties of the copper-containing oriented silicon steel.

[0039] In some optional embodiments, the step of performing decarburization annealing on the steel strip after the first cold rolling to obtain the decarburization annealed steel strip includes: the temperature of the decarburization annealing can be 790-890°C.

[0040] In some optional embodiments, the decarburization annealing treatment time may be 5-8 minutes.

[0041] The conditions for the decarburization annealing treatment in the embodiment of the present application may also include: the atmosphere for the decarburization annealing treatment is a mixed gas of wet H2 and N2.

[0042] By controlling the temperature, time and atmosphere of the decarburization annealing treatment within the above-mentioned ranges, the oxygen content and carbon content in the strip after decarburization annealing can be within appropriate ranges, and the thickness of the oxide layer of the strip after decarburization annealing can be controlled within an appropriate range, thereby further improving the bottom layer quality of the copper-containing oriented silicon steel.

[0043] In some optional embodiments, in the step of performing decarburization annealing on the steel strip after the first cold rolling to obtain the steel strip after decarburization annealing, the carbon content in the steel strip after decarburization annealing is less than 30 ppm.

[0044] By setting the carbon content in the strip steel after decarburization annealing within the above range, it is possible to avoid excessive carbon content in the finished product, magnetic aging, and performance deterioration, thereby further improving the bottom layer quality of the copper-containing oriented silicon steel and further improving the surface quality of the copper-containing oriented silicon steel.

[0045] In some optional embodiments, the preparation method may further include performing a second cold rolling process on the steel strip after decarburization annealing to obtain the steel strip after the second cold rolling.

[0046] The thickness of the strip can be further reduced by a second cold rolling process.

[0047] In some optional embodiments, in the step of performing a second cold rolling treatment on the steel strip after decarburization annealing to obtain the steel strip after the second cold rolling, the thickness of the steel strip after the second cold rolling may be 0.18-0.30 mm.

[0048] The thickness of the strip after the second cold rolling is the thickness of the finished product.

[0049] The thickness of the strip can be further reduced by the second cold rolling process, thereby achieving the purpose of reducing iron loss by reducing the thickness.

[0050] In some optional embodiments, the preparation method may further include: coating the steel strip after the second cold rolling with a magnesium oxide layer, high temperature annealing, coating with an insulating layer, stretching and flattening annealing, and laser scoring.

[0051] The magnesium silicate bottom layer is formed in the high temperature annealing stage, and the high temperature annealing treatment includes the first stage heating and the first stage insulation, the second heating stage and the second insulation stage. Exemplarily, the strip is heated from 15-30°C to 550-750°C in the first stage, and the first stage insulation is carried out. The strip after the first stage insulation is heated from 550-750°C to 1100-1200°C in the second stage, and the second stage insulation is carried out. The magnesium silicate bottom layer is formed in the heating process from the end of the first stage insulation to the beginning of the second stage insulation, and the quality of the strip surface oxide layer before the formation of the magnesium silicate bottom layer determines the quality of the magnesium silicate bottom layer.

[0052] It is understandable that the magnesium silicate bottom layer is the middle layer connecting the insulating coating and the strip steel substrate. A good quality magnesium silicate bottom layer can improve the adhesion of the insulating coating. The magnesium silicate bottom layer is an inorganic non-metal and has a certain insulation property, which can further improve the insulation effect of the insulating coating. In addition, a good magnesium silicate bottom layer can also increase surface tension, improve magnetic properties, and improve surface finish.

[0053] The embodiment of the present application proposes a copper-containing oriented silicon steel, which is prepared by the preparation method of the present application.

[0054] The copper-containing oriented silicon steel of the embodiment of the present application has the same beneficial effects as the preparation method of the embodiment of the present application, which will not be described in detail here.

[0055] In some optional embodiments, the iron loss of the copper-containing oriented silicon steel is 0.78-1.02 W / kg, and the magnetic induction intensity of the copper-containing oriented silicon steel is greater than 1.89T.

[0056] Example

[0057] The following examples describe the disclosure of the present application in more detail, and these examples are for illustrative purposes only, as various modifications and variations within the scope of the disclosure of the present application are apparent to those skilled in the art. Unless otherwise stated, all parts, percentages, and ratios reported in the following examples are by mass, and all reagents used in the examples are commercially available or synthesized according to conventional methods and can be used directly without further treatment, and the instruments used in the examples are commercially available.

[0058] Example 1

[0059] A slab of copper-containing oriented silicon steel is provided, and the chemical composition of the slab is shown in Table 1. The slab is heated in a heating furnace at a heating temperature of 1290° C. and a holding time of 300 min, and then hot rolled to a thickness of 2.3 mm, and the final rolling temperature of the hot rolling treatment is 978° C. The hot-rolled strip is pickled and then subjected to a first cold rolling treatment, and the thickness of the strip after the first cold rolling is 0.65 mm. The strip after the first cold rolling is subjected to decarburization annealing treatment, the temperature of the decarburization annealing treatment is 840°C, the time of the decarburization annealing treatment is 6 minutes, and the strip after decarburization annealing is obtained. The carbon content of the strip after decarburization annealing is 22ppm, the oxygen content is 582ppm, and the thickness of the oxide layer of the strip after decarburization annealing is 7.5μm. The strip after decarburization annealing is subjected to a second cold rolling treatment to obtain a strip after the second cold rolling with a thickness of 0.265mm. Subsequently, the strip is coated with a magnesium oxide layer, subjected to high temperature annealing, coated with an insulating layer, subjected to stretching and flattening annealing, and subjected to laser scoring.

[0060] Example 2

[0061] A slab of copper-containing oriented silicon steel is provided, and the chemical composition of the slab is shown in Table 1. The slab is heated in a heating furnace at a heating temperature of 1295° C. and a holding time of 280 min, and then hot rolled to a thickness of 2.2 mm, and the final rolling temperature of the hot rolling treatment is 967° C. The hot-rolled strip is pickled and then subjected to a first cold rolling treatment, and the thickness of the strip after the first cold rolling is 0.575 mm. The strip after the first cold rolling was subjected to decarburization annealing treatment, the temperature of the decarburization annealing treatment was 835°C, the time of the decarburization annealing treatment was 5.5 minutes, and the strip after decarburization annealing was obtained. The carbon content of the strip after decarburization annealing was 21ppm, the oxygen content was 618ppm, and the thickness of the oxide layer of the strip after decarburization annealing was 8.4μm. The strip after decarburization annealing was subjected to a second cold rolling treatment to obtain a strip after the second cold rolling with a thickness of 0.193mm. Subsequently, the strip was coated with a magnesium oxide layer, subjected to high temperature annealing, coated with an insulating layer, subjected to stretching and flattening annealing, and subjected to laser scoring.

[0062] Example 3

[0063] A slab of copper-containing oriented silicon steel is provided, and the chemical composition of the slab is shown in Table 1. The slab is heated in a heating furnace at a heating temperature of 1318° C. and a holding time of 320 min, and then hot rolled to a thickness of 2.15 mm, and the final rolling temperature of the hot rolling treatment is 985° C. The hot-rolled strip is pickled and then subjected to a first cold rolling treatment, and the thickness of the strip after the first cold rolling is 0.635 mm. The strip after the first cold rolling was subjected to decarburization annealing treatment, the temperature of the decarburization annealing treatment was 845°C, the time of the decarburization annealing treatment was 6.5 minutes, and the strip after decarburization annealing was obtained. The carbon content of the strip after decarburization annealing was 26ppm, the oxygen content was 642ppm, and the thickness of the oxide layer of the strip after decarburization annealing was 7.8μm. The strip after decarburization annealing was subjected to a second cold rolling treatment to obtain a strip after the second cold rolling with a thickness of 0.225mm. Subsequently, the strip was coated with a magnesium oxide layer, subjected to high temperature annealing, coated with an insulating layer, subjected to stretching and flattening annealing, and subjected to laser scoring.

[0064] Example 4

[0065] A slab of copper-containing oriented silicon steel is provided, and the chemical composition of the slab is shown in Table 1. The slab is heated in a heating furnace at a heating temperature of 1278° C. and a holding time of 260 min, and then hot rolled to a thickness of 2.45 mm, and the final rolling temperature of the hot rolling treatment is 985° C. The hot-rolled strip is pickled and then subjected to a first cold rolling treatment, and the thickness of the strip after the first cold rolling is 0.735 mm. The strip after the first cold rolling was subjected to decarburization annealing treatment, the temperature of the decarburization annealing treatment was 865°C, the time of the decarburization annealing treatment was 7.5 minutes, and the strip after decarburization annealing was obtained. The carbon content of the strip after decarburization annealing was 28ppm, the oxygen content was 737ppm, and the thickness of the oxide layer of the strip after decarburization annealing was 8.8μm. The strip after decarburization annealing was subjected to a second cold rolling treatment to obtain a strip after the second cold rolling with a thickness of 0.285mm. Subsequently, the strip was coated with a magnesium oxide layer, subjected to high temperature annealing, coated with an insulating layer, subjected to stretching and flattening annealing, and subjected to laser scoring.

[0066] Example 5

[0067] Except that the chemical composition of the slab is different from that in Example 1, the rest of the preparation process is the same as that in Example 1. The chemical composition of the slab is shown in Table 1.

[0068] Comparative Example 1

[0069] Except that the chemical composition of the slab is different from that in Example 1, the rest of the preparation process is the same as that in Example 1. The chemical composition of the slab is shown in Table 1.

[0070] Comparative Example 2

[0071] Except that the chemical composition of the slab is different from that in Example 1, the rest of the preparation process is the same as that in Example 1. The chemical composition of the slab is shown in Table 1.

[0072] Comparative Example 3

[0073] Except that the chemical composition of the slab is different from that in Example 1, the rest of the preparation process is the same as that in Example 1. The chemical composition of the slab is shown in Table 1.

[0074] Table 1

[0075] Serial number C / % Si / % Als / % N / % Mn / % Cr / % Cu / % S / % Example 1 0.048 3.22 0.0185 0.0085 0.22 0.058 0.52 0.006 Example 2 0.035 3.14 0.0195 0.0098 0.12 0.083 0.48 0.0095 Example 3 0.043 3.24 0.0242 0.0105 0.28 0.102 0.58 0.004 Example 4 0.052 2.91 0.0169 0.0078 0.15 0.124 0.46 0.0076 Example 5 0.055 3.23 0.0218 0.0112 0.24 0.136 0.44 0.0058 Comparative Example 1 0.035 2.85 0.0272 0.0118 0.32 0.025 0.42 0.021 Comparative Example 2 0.026 3.15 0.0194 0.0081 0.09 0.036 0.48 0.018 Comparative Example 3 0.082 3.18 0.014 0.0092 0.26 0.018 0.69 0.008

[0076] Test Section

[0077] Visually observe the surface quality of the finished product.

[0078] Adhesion of the bottom layer: According to the national standard GB / T2522 "Test method for surface insulation resistance and coating adhesion of electrical steel sheets (strips): divided into four levels: A, B, C, and D. The reverse bending method is used to measure the adhesion of the coating.

[0079] Magnetic properties of finished products: According to the national standard "Method for measuring the magnetic properties of electrical steel sheets (strips) using a single-piece tester", the sample size is 500mm*500mm.

[0080] Example 2 Schematic diagram of the oxide layer structure of the strip steel after decarburization annealing treatment Figure 2 The schematic diagram of the oxide layer structure of the steel strip after decarburization annealing in comparative example 1 is shown in Figure 3 shown.

[0081] The test results of Examples 1-5 and Comparative Examples 1-3 are shown in Table 2.

[0082] Table 2

[0083] Serial number Adhesion grade Appearance quality <![CDATA[P 17 / 50 / W / kg]]> <![CDATA[B8 / T]]> Example 1 B Good gloss, no defects 0.942 1.912 Example 2 B Good gloss, no defects 0.838 1.892 Example 3 B Good gloss, no defects 0.783 1.901 Example 4 A Good gloss, no defects 1.015 1.916 Example 5 B Good gloss, no defects 0.982 1.905 Comparative Example 1 C Poor gloss, no defects 1.135 1.862 Comparative Example 2 D Surface spot leakage 1.216 1.824 Comparative Example 3 D Surface spot gold exposure 1.262 1.814

[0084] It can be seen from Examples 1-5 and Comparative Examples 1-3 that the Cu content in Comparative Example 3 is greater than 0.6%, which not only increases the cost, but also causes the surface quality of the copper-containing oriented silicon steel to deteriorate. In Examples 1-5, controlling the amount of Cr added is beneficial to increasing the thickness of the oxide layer and improving the structure of the oxide layer. The Cr content in Comparative Examples 1-3 is less than 0.05%, and its effect on the thickness and structure of the oxide layer is not obvious. In Comparative Example 1, the oxide layer thickness is less than 7μm, and the adhesion of the finished insulating coating is poor.

[0085] Although the present application has been described with reference to preferred embodiments, various modifications may be made thereto and parts thereof may be replaced with equivalents without departing from the scope of the present application. In particular, the various technical features mentioned in the various embodiments may be combined in any manner as long as there are no structural conflicts. The present application is not limited to the specific embodiments disclosed herein, but includes all technical solutions falling within the scope of the claims.

Claims

1. A method for preparing copper-containing oriented silicon steel, characterized in that: include: A slab of copper-containing oriented silicon steel is provided, wherein the slab comprises the following components, based on the total mass of the slab being 100%, C: 0.03%-0.06%, Si: 2.85%-3.45%, Als: 0.015%-0.025%, N: 0.0075%-0.0115%, Mn: 0.1%-0.3%, Cu: 0.4%-0.6%, S: 0.003%-0.010%, Cr: 0.05%-0.20%, and the remainder being Fe and unavoidable impurities; The slab is hot-rolled to obtain a hot-rolled steel strip, wherein the heating temperature of the hot-rolling process is 1250-1320° C.; Performing a first cold rolling process on the hot-rolled steel strip to obtain a first cold-rolled steel strip; The steel strip after the first cold rolling is subjected to decarburization annealing treatment to obtain the steel strip after decarburization annealing, wherein the oxygen content in the steel strip after decarburization annealing is 550-750 ppm, and the thickness of the oxide layer of the steel strip after decarburization annealing is 7-9 μm.

2. The method for preparing copper-containing oriented silicon steel according to claim 1, characterized in that: The step of hot rolling the slab to obtain hot rolled strip steel also includes: the final rolling temperature of the hot rolling treatment is 890-990°C.

3. The method for preparing copper-containing oriented silicon steel according to claim 1, characterized in that: The step of performing a first cold rolling treatment on the hot-rolled steel strip to obtain the first cold-rolled steel strip comprises: the thickness of the first cold-rolled steel strip is 0.5-0.8 mm.

4. The method for preparing copper-containing oriented silicon steel according to claim 1, characterized in that: The step of performing decarburization annealing treatment on the steel strip after the first cold rolling to obtain the decarburization annealed steel strip comprises: the temperature of the decarburization annealing treatment is 790-890°C.

5. The method for preparing copper-containing oriented silicon steel according to claim 1, characterized in that: In the step of performing decarburization annealing on the steel strip after the first cold rolling to obtain the decarburization annealed steel strip, the carbon content in the decarburization annealed steel strip is less than 30 ppm.

6. The method for preparing copper-containing oriented silicon steel according to claim 1, characterized in that: The preparation method further comprises performing a second cold rolling process on the decarburization annealed steel strip to obtain the second cold rolled steel strip.

7. The method for preparing copper-containing oriented silicon steel according to claim 6, characterized in that: In the step of performing a second cold rolling treatment on the decarburization annealed steel strip to obtain the second cold rolled steel strip, the thickness of the second cold rolled steel strip is 0.18-0.30 mm.

8. The method for preparing copper-containing oriented silicon steel according to claim 6, characterized in that: The preparation method further comprises: coating the steel strip after the second cold rolling with a magnesium oxide layer, performing high temperature annealing, coating an insulating layer, performing stretching and flattening annealing, and performing laser scoring.

9. A copper-containing oriented silicon steel, characterized in that: It is prepared by the preparation method according to any one of claims 1 to 8.

10. The copper-containing oriented silicon steel according to claim 9, characterized in that: The iron loss of the copper-containing oriented silicon steel is 0.78-1.02 W / kg, and the magnetic induction intensity of the copper-containing oriented silicon steel is greater than 1.89 T.

Citation Information

Patent Citations

  • Process for producing grain-oriented magnetic steel sheet with high magnetic flux density

    CN101432450A

  • Method for manufacturing grain-oriented electrical steel sheet

    CN113286909A

  • Copper-containing general oriented silicon steel and preparation method thereof

    CN114150126A

  • Copper-containing oriented silicon steel with excellent bottom layer adhesiveness and preparation method of copper-containing oriented silicon steel

    CN115161455A

  • Production method for improving electromagnetic performance and bottom layer quality of copper containing orientation silicium steel

    CN1786248A